Pengaruh Stres Kerja Dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan Pada Matahari Bungalow Restaurant And Spa Legian Kuta-Bali - Dewi, Putu Enika Lestari; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen, 2015)
This research was conducted on employees Matahari Bungalow. The samples used were 60 employees with saturated sampling method, sampling method is a method of using a saturated the entire population of the research samples. Data collection was conducted interviews, surveys, and questionnaires. The data analysis technique used is multiple linear regression analysis, as well as using the F test and t test. The results showed that job stress and significant negative effect on employee job satisfaction of employees at Matahari Bungalow while working motivation and significant positive effect on employee job satisfaction at Matahari Bungalow. Work motivation has a greater influence on job satisfaction in the Matahari  Bungalow.
Keywords: stres kerja; motivasi kerja; kepuasan kerja